THE EFFECT OF CONTENT SCHEMA ON THE READING COMPREHENSION: A PERSPECTIVE OF GRADE 12TH STUDENTS (Contemporary Journal of Social Science Review, 2025)
In the Khyber Pakhtunkhwa province of Pakistan, rural students share socioeconomic backgrounds, and educational experiences yet lack motivation to engage with reading comprehension due to rote-teaching methods. Their comprehension skills suffer, as they rely on memorisation, translation, and ready-made notes, leading to high failure rates and a fear of understanding texts. This study evaluated a content schema teaching strategy to improve reading comprehension using English textbook passages. Fifty-one grade-12 Pre-Medical students (ages 18–21) from Government Higher Secondary School, Manyal, Dir Lower, participated in a quasi-experimental mixed-method design, non-randomly assigned to experimental and control groups. Assessment tools included pre- and post-tests, and semi-structured interviews with 12 key informants, which were analysed thematically. Results indicated that activating content schema, providing background knowledge related to text topics, enhanced students’ ability to interpret passages, broadened their perspectives, and boosted confidence. Interviewees reported greater comprehension and critical thinking in lessons. Findings suggest replacing traditional recitation methods with content schema strategies to foster deeper understanding and practical learning in reading comprehension classrooms at the secondary level. Future research could explore the applications of this strategy. Results underscore the strategy’s potential for adoption.